Mechanism analysis of humification coupling metabolic pathways based on cow dung composting with ionic liquids. (1st January 2023) - Yang, Hongxiang; Ma, Liangcai; Fu, Mengxin; Li, Kecheng; Li, Yinzhong; Li, Qunliang
Abstract: This study focused on how adding ionic liquids (IL) affects composting humification. During the warming and thermophilic phases, addition of IL increased precursors content, and increased the polymerization of humus (HS) at later stages. Furthermore, the final HS and humic acid (HA) content of experimental groups (T) groups 129.79 mg/g and 79.91 mg/g were higher than in control group (CK) 118.57 mg/g and 74.53 mg/g, respectively (p < 0.05). IL up-regulated the gene abundance of metabolism for carbohydrate and amino acid (AA), and promoted the contributions of Actinobacteria and Proteobacteria, which affected humification. The redundancy analysis (RDA) results showed that the citrate-cycle (TCA cycle)(ko0020), pentose phosphate pathway (ko00030), pyruvate metabolism (ko00620), glyoxylate and dicarboxylate metabolism (ko00630), propanoate metabolism (ko00640), butanoate metabolism (ko00650) positively correlated with HA and HI. HA and humification index (HI) positively correlated with AA metabolic pathways, and fulvic acid (FA) was negatively correlated with these pathways. Overall, metabolism for carbohydrate and AA metabolism favored compost humification. ILs improved metabolism for carbohydrate and amino acid metabolism, thus enhancing humification. Graphical abstract: Image 1 Highlights: 1.IL promoted the humification process in composting. 2.IL up-regulated the genes abundance of carbohydrate and amino acid metabolism. 3.IL enhanced the contribution of Actinobacteria and Proteobacteria. 4.Amino acid metabolism facilitated the conversion of FA to HA.